Influence of the external breast prosthesis on the postural control of women who underwent mastectomy: Cross-sectional study - Koralewska, Anna; Domagalska-Szopa, Małgorzata; Łukowski, Robert; Szopa, Andrzej (Frontiers in Oncology, 2022)
Background: Women after mastectomy may decide to either have a breast reconstruction or use an external breast prosthesis. Aim: The aim of the presented research was to evaluate the influence of external breast prosthesis on postural stability in women after mastectomy. Methods and Procedures: In the study 52 women after unilateral mastectomy took part. The study consisted of 4 parts: 1) anthropometric measurements; 2) measurements of upper limb circumference; 3) assessment of weight-bearing (WB); and 4) posturographic tests (PT). Outcomes and Results: Differences in the arm circumferences on the amputated (A) and non-amputated (NA) sides did not confirm the occurrence of lymphedema in limb on amputated side. The results of the WB between the A and NA body sides in both tested conditions, i.e., with open and closed eyes, showed no significant differences between the test with and without an external prosthesis. No statistically differences have been observed between posturometric parameters with and without breast prosthesis during both PT. In comparing the posturometric parameters between the PT with open and closed eyes, the sway path of the center of pressure was statistically significantly longer when eyes were closed in both conditions, i.e., with and without breast prosthesis. Conclusion and Implications: The finding show that 1) external breast prosthesis does not have a significant influence on the symmetry of loading on the A and NA body sides and on the postural stability of women after unilateral mastectomy and 2) exclusion visual control during PT increases postural instability in women after unilateral mastectomy.